Dual Cross-Talk between Nitric Oxide and D-Serine in Astrocytes and Neurons in the Brain - Darra, Elena; Ebner, Florian H.; Shoji, Kazuo; Suzuki, Hisanori; Mariotto, Sofia (Central Nervous System Agents in Medicinal Chemistry, 2009)
The present review describes the role of the putative cross-talk between two neurotransmitters, nitric oxide (NO) and D-serine, in the brain. Under physiological conditions NO homeostasis guarantees the correct function of NO in a number of events in the brain such as neurotransmission and vascular tone regulation. D-serine, produced in astrocytes, acts synergistically with glutamate at NMDA receptors on postsynaptic neurons. Neuronal and endothelial NO synthase (nNOS and eNOS) in astrocytes cross-talk with serine racemase (SR) and D-amino acid oxydase (DAAO), catalyzing the synthesis and degradation of D-serine, respectively. SR is inhibited by NO which activates DAAO. D-serine inhibits nNOS but not eNOS and activates SR. Astrocytes and neurons also cross-talk through NO/D-serine system. D-serine released from astrocytes induces a rapid increase in NO contents in postsynaptic neurons. Overall, D-serine production in astrocytes is negatively regulated by NO. Under inflammatory conditions, pro-inflammatory cytokines or Aβ induce, first, a drop in NO contents and an increase in the amounts of D-serine in astrocytes. Together with enhanced glutamate release from presynaptic neurons, D-serine induces an increase in Ca2+ up-take into presynaptic neurons. In astrocytes an initial drop in NO contents triggers NF-κB activation followed by inducible NOS (iNOS) expression. iNOS-derived massive amounts of NO may potentially be toxic. Under schizophrenic conditions, D-serine production is down-regulated. Together with reduced glutamate release, this situation leads to the decreased NO production in postsynaptic neurons. In astrocytes induction of iNOS expression becomes predominant. Initial drop in nNOS-derived NO is potentially toxic in this scenario.